Credit access, productivity and poverty reduction in Malawi: a conditioned mixed process approach - Blessings Bolola Nyirongo (Discover Agriculture, 2025)
Abstract Most policy discussions have been centred on improving smallholder farmers’ agricultural productivity as a way of reducing poverty in SSA. IFAD acknowledges that higher agricultural productivity can hasten sustainable agriculture development and poverty reduction in SSA countries which calls for higher productivity among smallholder farmers if we are to attain higher levels of economic growth. Credit access plays an important role in predicting the productivity and poverty levels among smallholder farmers. The study employs the use of a conditioned mixed process model on 4,268 maize-producing farmers to understand the nexus between credit access, productivity and poverty reduction among smallholder farmers in Malawi. Smallholder farmers with credit access hold a higher productivity than their counterparts which underpins the idea that agricultural productivity is key in improving the productivity of smallholder farmers. However, the study couldn’t find a direct relationship between credit access and poverty reduction. Rather, access to credit has a secondary effect on poverty alleviation through productivity enhancement. The study found a constructive relationship between agricultural productivity growth and poverty reduction. The study concludes that improving agricultural productivity is key to plummeting the high poverty levels among smallholder farmers. Therefore, the study recommends widening access to credit programs, provision of no or little collateral loans, and provision of agricultural credit to increase productivity and lower poverty levels among smallholder farmers in Malawi. However, the study failed to address all forms of poverty hence a need for further research on the same.